Mobile phone marketing - Baack, Daniel W., (SAGE knowledge. Cases., 2016)
There is ever-increasing competition in the international mobile phone market. Therefore, in order to be successful, mobile phone companies must come up with creative new marketing and advertising campaigns. This case study follows one such success story, in the form of the Nokia N8 campaign in the Philippines.